Analysis of the effects of macroeconomic factors on entrepreneurship: An application on E7 countries - Ersin, İrfan; Karakeçe, Ercan (IGI Global, 2022)
Entrepreneurship is an important field in the increase and diversification of investments in a country. Entrepreneurship is gaining importance in today's world where financial marketing has become an important sector. The aim of this study is to determine the macroeconomic factors that determine entrepreneurship in E7 countries. In the study using logit method, the period of 1992-2018 was discussed. In the analysis results, the variables of unemployment, financial loans and current account deficit were found to be macroeconomic factors determining entrepreneurship. Given that entrepreneurship is important in the financial field, E7 countries should take into account the financial credit markets, focus on economic policies to reduce unemployment and address the current account deficit problem.
Keywords: Macroeconomic; E7 Countries; Entrepreneurship